Meningkatkan Religiusitas Masyarakat melalui Kajian Kitab Bidayatul Hidayah - M. Zunaidul Muhaimin; Nunik Zuhriyah (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2024)
The cultural change of the society affects the level of understanding of the religion of the people, the low religious awareness and the quality of human resources as well as the still low economy resulted in the lower religiousness of the Ringinsari Kulon society. This research is a type of qualitative examination using the Participatory Action Research (PAR) approach that is between the subject of research and the researcher as an initiator. Researchers dig data through in-depth observations and interviews to explore data collected as secondary data through interactive methods, data analyzed descriptively to draw conclusions. The purpose of this study is to know the understanding of the Ringinsari Kulon people of Kediri city of the book of the Hidayat Hidayah and live it and know the improvement of the quality of the religious attitude of the ringinsari kulon people to the book. The results of this survey show that the rise in the religiousness of the community can be seen from the relatively increased number of jamaahs and adolescents who follow the study, the intensity of the five-time worship in the Ar-Rahman Mosque, the shift in the way the adolescents dress around the Ramadan Mosque with decent clothing as well as the number of adolescents turning to the mosque to attend the study.